Measures of strength and jump performance can predict 30-m sprint time in rugby union players - Furlong, L. A. M.; Harrison, A. J.; Jensen, R. L. (The Journal of Strength and Conditioning Research, 2021)
Performance and fitness monitoring in Rugby Union often include jumping, sprinting, and strength tests, but repeatability of and relationships between these measures are unclear. The level of interindividual variability in these relationships and their sprint time predictive capabilities are also unknown. This study examined the reliability of, and relationship between, countermovement (CMJJH), squat (SJJH), and rebound (RBJJH) jump heights, rebound jump contact time (RBJCT), estimated 1 repetition maximum back squat relative to body mass (SQBM), and reactive strength index (RSI) to 30-m sprint time of subelite, semiprofessional Rugby Union players. Measurement reliability was very good, with high average intraclass correlation coefficients (=0.9) and low coefficient of variation (<10.1%). All variables were significantly (p < 0.01) correlated to each other (r > 0.575), except for SQBM (only related to CMJJH, r = 0.621) and RBJCT (only related to RSI, r = -0.727). SJJH and SQBM were the strongest and most consistent predictors of time to 30 m (R = 0.754 ± 0.081; SEE = 0.166 ± 0.025), but variability in SEE magnitude was observed across the group during bootstrapping. Cross-validation showed a mean difference between actual and predicted 30 m times equivalent to 0.22% of the group average time to 30 m. These results support the importance of multiple aspects of fitness training in Rugby Union players for improving performance in short-duration sprinting activities, but highlight the individual nature of their relative importance. Measures of strength and power can be used to predict short sprint performance by the strength and conditioning professional.